Carbonized polyaniline coupled molybdenum disulfide/graphene nanosheets for high performance lithium ion battery anodes. Issue 117 (10th November 2015) - Han, Sheng; Ai, Yani; Tang, Yanping; Jiang, Jianzhong; Wu, Dongqing
Abstract : Carbonized polyaniline coupled molybdenum disulfide and graphene show excellent electrochemical performances as an anode material for lithium ion batteries. Abstract : Two-dimensional molybdenum disulfide/graphene hybrids wrapped in carbonized polyaniline (MCGs) have been constructed by the in situ growth of molybdenum trisulfide nanoparticles on polyaniline decorated graphene oxide nanosheets and the following carbonization. When the resulting hybrids were used as anode materials in lithium ion batteries, the carbonized polyaniline can effectively prevent the pulverization of MoS2 caused by the inner-plane volume expansion. It turns out that MCG-600, the sample thermally treated at 600 °C, manifests a capacity of 785 mA h g −1 after 300 cycles at the current density of 200 mA g −1 and a capacity of 724 mA h g −1 even at a high current density of 1 A g −1 .